Arsenic in rice and rice straw (Bangladesh Veterinarian, 2012)
Arsenic from groundwater affects people in Bangladesh via seed grains and forages. Samples of rice (Oryza sativa L) and rice straw were collected from arsenic-contaminated areas and arsenic concentration was measured using Flow Injection Hidride Generator Atomic Absorption Spectrophotometer (FI-HG-AAS) method. The concentrations in rice and rice straw were 0.235 ± 0.014 ppm (n = 48) and 1.149 ± 0.119 ppm (n = 51), respectively. Both were greater than the maximum permissible concentration in drinking water (0.05 ppm; WHO). DOI: http://dx.doi.org/10.3329/bvet.v29i1.11883 Bangl. vet. 2012. Vol. 29, No. 1, 1-6